Innovations in Addressing Mental Health Needs in Humanitarian Settings: A Complexity Informed Action Research Case Study - Parrish-Sprowl, Susan; Parrish-Sprowl, John; Alajlouni, Samia (Frontiers in Communication, 2020)
Addressing mental health challenges in humanitarian settings, where needs are many and resources are scarce, requires innovative solutions. In this manuscript, we describe a quantum complexity informed intervention, Communication for Whole Health (CWH), created for a large Jordanian healthcare NGO to address mental health needs of patients and staff. In the humanitarian aid context, this health domain is referred to by the acronym MHPSS (mental health and psychosocial support). The focus of this participatory action research case study is the collaborative elaboration of an MHPSS intervention in one of the NGO’s urban primary healthcare clinics, serving mostly Syrian refugees. The intervention capitalizes on the synergistic effects generated from the systemic nature of communication where every interaction is an intervention, and the health implications of research demonstrating communication is bioactive. Rather than treating mental health as an add-on medical specialty targeting patients with “psychiatric disorders,” systemic MHPSS starts from the premise that everyone has mental health, which is inextricably linked to physical and social health. Emphasis is on integrating awareness of mental health as part of whole health and taking advantage of every interaction to facilitate well-being for patients and staff. The intervention facilitated the transformation of the communication ecology of the clinic from a culture of reactivity to a culture of receptivity by strengthening communication resources and practices. Staff reported feeling more empowered to help patients and displayed increased motivation to find innovative ways to use available resources. They felt better equipped to manage their own stress response and support coworkers. Patients learned basic stress management skills to better control chronic health conditions and reported sharing this information with family members. Staff reported many examples of patients responding positively to interventions to reduce patient reactivity, leading to beneficial behavior change and improved health outcomes. Results suggest a systemic MHPSS approach can contribute to ameliorating health inequities by expanding resources for patients and staff, thus empowering them to act into their current circumstances to support whole health. The CWH approach has potential in similar contexts to address mental health needs in a cost-effective and impactful way.